2022
DOI: 10.1002/jmv.27781
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and inflammatory biomarkers in herpes zoster

Abstract: The risk of herpes zoster (HZ) increases as cell-mediated immunity declines with age.Even though oxidative stress plays a crucial role in the development of HZ, there are few serum biomarkers of the disease's antioxidant activity. The purpose of this study is to investigate the blood levels of major antioxidants in HZ patients. To the best of our knowledge, this is the first study on this issue in the literature. The serum levels of antioxidants including uric acid (UA), total bilirubin (TBİL), albumin (ALB), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Moreover, SUA's multifaceted physiological effects, such as antioxidant effects and mediation of autoimmune diseases, are indicative of the crucial role it could play in the human body. [26,27] However, the study by Ghamri RA et al [23] reported no significant association between Table 3 Relationship between SUA (100μmol/L) and TGs (mmol/L) in diferent models.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, SUA's multifaceted physiological effects, such as antioxidant effects and mediation of autoimmune diseases, are indicative of the crucial role it could play in the human body. [26,27] However, the study by Ghamri RA et al [23] reported no significant association between Table 3 Relationship between SUA (100μmol/L) and TGs (mmol/L) in diferent models.…”
Section: Discussionmentioning
confidence: 98%
“…Our implication is that most of the NETosis targeted inhibitors will show their potential effectiveness against ocular herpetic infection as well. For instance, the NADPH- and/or ROS-inhibiting pharmacological compounds such as diphenyleneiodonium chloride (DPI) and N -acetylcysteine (NAC) suppress NETosis, and many reports suggest reduction in ocular herpes infection when treated with antioxidants because it has been reported that HSV infection may be exacerbated by a cellular state of oxidative stress, while augmented intake of antioxidants might avert replication of the virus [ 100 , 101 , 102 , 103 , 104 ]. Furthermore, ROS inhibit NF-kB (Nuclear Factor kappa-light-chain-enhancer of activated B cells) translocation, which is a known marker for aggravated ocular HSV-1 infection [ 105 ].…”
Section: Diagnosis and Therapeuticsmentioning
confidence: 99%
“…The results suggested that patients with chronic HZ pain were more likely to have poor pain control than those with acute HZ pain, which might be related to central sensitization. In addition, ALB Subacute phase vs acute phase c Chronic phase vs acute phase *Statistical significance levels in the poor control group were low, which might be related to deficits in nutritional status, weak physical condition, and low immunity [32].…”
Section: Rbc Countmentioning
confidence: 99%